Recycling waste for energy: Reusing methyl orange dye-adsorbed polythiophene/Fe3O4 nanorods/reduced graphene oxide nanocomposite as a supercapacitor electrode - Ahmad Husain; Asim Ali; Sara A. Alqarni; Khalid Ansari; Mohtaram Danish; Prem Gunnasegaran; Mohammad Kanan; Jayant Giri; M. Kandasamy; M.M.A. Khan; Kyeong Tae Kang (Journal of Science: Advanced Materials and Devices)
This study presents a sustainable waste-to-wealth approach by repurposing methyl orange (MO) dye-adsorbed polythiophene/iron oxide/reduced graphene oxide nanocomposite (PTh/Fe3O4/RGO) for dual functionality in wastewater treatment and energy storage. PTh/Fe3O4/RGO nanocomposite was initially employed as an effective adsorbent to remove harmful MO dye from wastewater. After successful adsorption, the dye-saturated PTh/Fe3O4/RGO was repurposed as a supercapacitor electrode to investigate its energy storage capabilities. Electrochemical tests before MO adsorption revealed that the pristine PTh/Fe3O4/RGO electrode demonstrated promising performance with a specific capacitance of 467.3 Fg−1 at 1 Ag−1 and excellent cyclic stability of 95.3% retention over 5000 Galvanostatic charge-discharge (GCD) cycles. Further, the maximum adsorption of MO by the PTh/Fe3O4/RGO was achieved under optimal conditions: pH 3, 2.5 gL−1 dosage, 120 min contact time, and 50 mgL−1 MO concentration. The adsorption behaviour was well-explained by the Langmuir isotherm, pseudo-second-order kinetics, and Dubinin-Radushkevich (D-R) isotherm, indicating a physical adsorption process with a monolayer capacity of 151.34 mgg−1. Thermodynamic analysis, with a positive enthalpy (ΔH°) and negative Gibbs free energy (ΔG°), confirmed that the process is endothermic and spontaneous. Desorption studies showed that 88.72% of the MO could be desorbed in the first cycle, with effective regeneration up to six cycles using NaOH. Post-adsorption, the material still retained significant supercapacitor properties, with a specific capacitance of 380.9 Fg−1 at 1 Ag−1 and 83.2% cyclic stability over 5000 GCD cycles. This study demonstrates a circular, sustainable approach that integrates waste treatment with energy storage, highlighting the potential of reusing materials for multifunctional applications.